2008
DOI: 10.5194/npg-15-275-2008
|View full text |Cite
|
Sign up to set email alerts
|

Combination of different types of ensembles for the adaptive simulation of probabilistic flood forecasts: hindcasts for the Mulde 2002 extreme event

Abstract: Abstract. Flood forecasts are essential to issue reliable flood warnings and to initiate flood control measures on time. The accuracy and the lead time of the predictions for head waters primarily depend on the meteorological forecasts. Ensemble forecasts are a means of framing the uncertainty of the potential future development of the hydro-meteorological situation.This contribution presents a flood management strategy based on probabilistic hydrological forecasts driven by operational meteorological ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…It has a total area of 336 km 2 , which is considerably smaller than most catchments, and even sub-catchments, referred to in the current literature on ensemble streamflow forecasting (e.g. Dietrich et al, 2008;Jaun and Ahrens, 2009;Thielen et al, 2009b;Reggiani et al, 2009). Earlier studies have shown that forecast skill depends on temporal and spatial scales.…”
Section: Scope Of the Present Papermentioning
confidence: 99%
“…It has a total area of 336 km 2 , which is considerably smaller than most catchments, and even sub-catchments, referred to in the current literature on ensemble streamflow forecasting (e.g. Dietrich et al, 2008;Jaun and Ahrens, 2009;Thielen et al, 2009b;Reggiani et al, 2009). Earlier studies have shown that forecast skill depends on temporal and spatial scales.…”
Section: Scope Of the Present Papermentioning
confidence: 99%
“…For the very small Wiltzsch sub-catchment, a contributing area of a reservoir, the model was only calibrated for the flood event evaluated within this case study. All hourly simulations started seven days before the chosen event for an optimal adjusting of initial model conditions, which had been computed by a continuous long time model run with daily time steps before (Dietrich et al, 2008). We calculated the following objective indicators of performance for the events four and five:…”
Section: Performance Criteriamentioning
confidence: 99%
“…We used the conceptual hydrological model ArcEGMO (Becker et al, 2002), which is in wide use for its short computational time, its flexibility in spatial, temporal and structural resolution and the mainly GIS-based assignment of parameters. The model was calibrated for the Mulde catchment for flood events from 1954 to 2006 using precipitation data from a) recording stations with high temporal resolution and b) disaggregated time series from stations with daily records (Dietrich et al, 2008). The upper Mulde catchment is situated in the Ore Mountains, whereas several sub-catchments drain from South to North.…”
Section: Performance Criteriamentioning
confidence: 99%
“…Ensemble flood forecasting based on operational forecasts of the regional Eta EPS in the Taquari-Antas basin To derive streamflow forecasts, the hydrological model was forced with observed rainfall up to the start of forecast, and then coupled to deterministic QPF and each one of the ensemble members (herein referred to the HEPS). In addition, a combination of current forecasts with earlier model runs, known as Lagged Averaged Forecasts -LAF (DIETRICH et al, 2008), was adopted in order to increase the number of hydrological ensemble members without extra computational cost. The procedure used to generate the lagged forecasts was similar to that presented by Machado et al (2010), but in this case considering the hydrological forecasts instead of the meteorological ones.…”
Section: Quantitative Precipitation Data and Generation Of Hydrologicmentioning
confidence: 99%
“…In this approach, a set of possible future states of the atmosphere can be provided through small perturbations in the initial conditions of a control forecast (BUIZZA, 1997), different physical representations and changes in parameterization schemes of atmospheric models (STENSRUD; BAO;WARNER, 2000;WANDISHIN et al, 2001), or combination of previous forecasts with the most recent ones (DIETRICH et al, 2008;MACHADO et al, 2010). These systems have achieved consistent recognition for the improvement of weather forecast skill, leading hydrological research towards the development of Hydrological Ensemble Prediction Systems -HEPS (e.g.…”
Section: Introductionmentioning
confidence: 99%